Exile and post-1946 Haitian literature : Alexis, Depestre, Ollivier, Laferrière, Danticat - Munro, Martin (Contemporary French and francophone cultures, 2007)
Haitian writing is one of the richest literary traditions in the Americas, and yet is little known outside of Haiti. This book is an introduction to this literature, focusing on the period from 1946 to the present, a time in which exile has become the dominant theme in Haitian writing. Reading post-1946 Haitian writing as a literature of exile, the chapters analyze key novels by the most important figures of each generation: Jacques-Stephen Alexis, René Depestre, Émile Ollivier, Dany Laferrière, and Edwidge Danticat. The emphasis is on close, detailed readings, and on understanding the particu.